(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study was to determine the prevalence of arteriovenous fistulas (AVFs) and its consequences in patients receiving haemodialysis (HD) in Vadodara, Gujarat. Methods: This was a prospective hospital-based study involving 196 individuals over the age of 18 who were on dialysis in two Vadodara hospitals. A pretested questionnaire was used to gather and document data, which included sociodemographic information as well as information about fistula-related problems. The hospital records were also checked to see if the complication and risk factors were the same. SPSS software version 23 was used to run appropriate statistical tests and analyse the data. The majority of the research patients were between the ages of 41 and 60, with male and female prevalence rates of 49.5 percent and 50.5 percent, respectively. Hypertension was the most common chronic ailment among the patients (41.7%), and more than 30.6 percent had several chronic illnesses. Radio cephalic fistula was the most prevalent kind of AVF (RCF). Ischemic neuropathy was the most common consequence linked with AVF patients (29.6 percent). Non-smokers had a lower risk of myocardial infarction than smokers. Conclusion: For successful care of AVF problems, early and prompt discovery is critical. The difficulties associated with AVF should be well-understood by health professionals. To improve the quality of life of patients with HD, early diagnosis and adequate treatment are critical.